Popup republic : how to start your own successful pop-up space, shop, or restaurant - Baras, Jeremy, 1988- (Hoboken, NJ : Wiley, 2015)
"PopUp Republic delves into the $50-billion dollar pop-up industry and includes stories, examples, anecdotes, case studies and a how-to guide of how to create a successful pop-up. Based on Baras' broad experience and unparalleled knowledge, PopUp Republic covers all aspects of pop-ups, including an evaluation of the U.S. vs. European/world pop-up markets; tools needed to create successful pop-ups; what constitutes a pop-up; the costs and benefits of pop-ups; what permits, insurance and licenses are needed to open a pop-up; and much more. More than just an A-to-Z guide on how to launch and operate a successful pop-up, PopUp Republic shows how pop-ups are disrupting the retail, dining and entertainment industries in this country and around the world"--
Preface -- Acknowledgments -- Introduction -- Section 1. The pop-up industry. Chapter 1. What is a pop-up? ; Chapter 2. The makings of PopUp Republic ; Chapter 3. Pop-ups: the state of the nation ; Chapter 4. Pop-ups: the state of the world ; Chapter 5. The size of the pop-up industry in the United States (a case study) ; Chapter 6. The case for pop-up urbanism as a tool to vitalize local economies ; Chapter 7. Interview with an urban economic development professional about pop-ups -- Section 2. Becoming a "popupreneur". Chapter 8. Are you a good candidate to host a pop-up? ; Chapter 9. A day in the life of a popupreneur ; Chapter 10. Choosing a concept ; Chapter 11. Creating a concept vs. creating a concept that sells ; Chapter 12. What to expect ; Chapter 13. How to manage it all ; Chapter 14. The day-to-day ; Chapter 15. What is success? ; Chapter 16. Customers -- Section 3. The execution. Chapter 17. Pop-up shops ; Chapter 18. Interview with Greg Spielberg, founder of Imagination in Space ; Chapter 19. Pop-up restaurants ; Chapter 20. Food trucks ; Chapter 21. Interview with Jeff Wang, owner of Yum Dum Food Truck ; Chapter 22. Fashion trucks ; Chapter 23. Interview with Laura Layton, owner of Tin Lizzy Fashion Truck ; Chapter 24. Pop-up spaces ; Chapter 25. Interview with Aaron Gadiel, shopping center executive ; Chapter 26. Farmers markets ; Chapter 27. Flea markets ; Chapter 28. Yard sales ; Chapter 29. The ideal pop-up customer: why you should target millennials ; Chapter 30. Case study: the launch of a pop-up store ; Chapter 31. Pop-up checklist -- Section 4. What's ahead. Chapter 32. Reload, fire, aim ; Chapter 33. Interview with Shuchi Naidoo, founder of 29 Calories pop-up restaurant ; Chapter 34. Look out! Here come the big brands and big malls ; Chapter 35. Interview with Melinda Holland, SVP of business development for General Growth Properties ; Chapter 36. Interview with Patty Hirt, retail development for General Growth Properties ; Chapter 37. Pop-ups: why they are becoming permanent ; Chapter 38. Pop-ups and baby boomers: a perfect fit -- About the author -- Index .
Includes index.
Machine generated contents note: Preface Acknowledgments Introduction Section 1: The Pop-Up Industry Chapter 1: What Is a Pop-Up? Chapter 2: The Makings of PopUp Republic Chapter 3: Pop-Ups: The State of the Nation Chapter 4: Pop-Ups: The State of the World Chapter 5: The Size of the Pop-Up Industry in the United States (a Case Study) Chapter 6: The Case for Pop-Up Urbanism as a Tool to Vitalize Local Economies Chapter 7: Interview with an Urban Economic Development Professional About Pop-Ups Section 2: Becoming a "Popupreneur" Chapter 8: Are You a Good Candidate to Host a Pop-Up? Chapter 9: A Day in the Life of a Popupreneur Chapter 10: Choosing a Concept Chapter 11: Creating a Concept vs. Creating a Concept That Sells Chapter 12: What to Expect Chapter 13: How to Manage It All Chapter 14: The Day-to-Day Chapter 15: What Is Success? Chapter 16: Customers Section 3: The Execution Chapter 17: Pop-Up Shops Chapter 18: Interview with Greg Spielberg, Founder of Imagination in Space Chapter 19: Pop-Up Restaurants Chapter 20: Food Trucks Chapter 21: Interview with Jeff Wang, Owner of Yum Dum Food Truck Chapter 22: Fashion Trucks Chapter 23: Interview with Laura Layton, Owner of Tin Lizzy Fashion Truck Chapter 24: Pop-Up Spaces Chapter 25: Interview with Aaron Gadiel, Shopping Center Executive Chapter 26: Farmers Markets Chapter 27: Flea Markets Chapter 28: Yard Sales Chapter 29: The Ideal Pop-Up Customer: Why You Should Target Millennials Chapter 30: Case Study: The Launch of a Pop-Up Store Chapter 31: Pop-Up Checklist Section 4: What's Ahead Chapter 32: Reload, Fire, Aim Chapter 33: Interview with Shuchi Naidoo, Founder of 29 Calories Pop-Up Restaurant Chapter 34: Look Out! Here Come the Big Brands and Big Malls Chapter 35: Interview with Melinda Holland, SVP of Business Development for General Growth Properties Chapter 36: Interview with Patty Hirt, Retail Development for General Growth Properties Chapter 37: Pop-Ups: Why They Are Becoming Permanent Chapter 38: Pop-Ups and Baby Boomers: A Perfect Fit About the Author Index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Retail trade -- Seasonal variations -- United States; Small business marketing -- United States; Store location -- United States; New business enterprises -- United States; Retail trade -- Seasonal variations -- Europe; Small business marketing -- Europe; Store location -- Europe; New business enterprises -- Europe; Magasins -- Localisation; Nouvelles entreprises; Magasins -- Localisation -- Europe; Nouvelles entreprises -- Europe; BUSINESS & ECONOMICS -- Entrepreneurship; New business enterprises; Retail trade -- Seasonal variations; Small business marketing; Store location; Europe; United States